The capability of harvestable slot-length limit regulation in conserving large and old northern pike (Esox lucius) - Tiainen, Joni Matias; Olin, Mikko Johannes; Lehtonen, Hannu Väinö Tapani; Nyberg, Kari Börje; Ruuhijärvi, Jukka (Finnish Environment Institute, 2017)
In this experimental fisheries regulation study, we compared the effects of size-selective fishing according to minimum length limit (MLL, 40 cm) or harvestable slot-length limit (HSL, 40–64.9 cm) on population density, biomass, size and age structures, and sex ratio of the northern pike (Esox lucius). Data were collected during the years 2006–2013 in four 2.1–13.8 ha pristine forest lakes in southern Finland. In lakes where MLL fishing was carried out, pike density, biomass and size structure showed greater negative responses than in lakes where HSL fishing was carried out: mean length and age decreased, and large pike (≥ 65 cm) disappeared in just four years. HSL fishing affected the pike to a lesser extent, and large pike remained in the lakes, which is considered an essential feature of sustainable fishing. However, the results suggest that the number of large pike may decrease even under the HSL fishing strategy if the growth rate is slow and fishing is intensive, due to the high possibility of fish being caught before reaching the length beyond the upper HSL limit. Peer reviewed